The Hidden Ontology of Language: A Structuralism Resolution to the Measurement Problem in Quantum Mechanics - Belay Sitotaw Goshu; Muhammad Ridwan; Ramlan (Britain International for Academic Research (BIAR-Publisher), 2025)
The quantum measurement problem continues to challenge classical ontological assumptions embedded in scientific discourse. Substantialist interpretations presume independent entities bearing definite properties, while instrumentalist approaches reduce quantum theory to predictive formalism, both retaining subject-predicate grammar that imposes classical categories onto quantum phenomena. Recent relational interpretations argue that quantum mechanics demands a fundamentally different descriptive mode, one that privileges interdependence and syntactic structure over Substantialist predication. This study explores the linguistic dimensions of quantum entanglement and measurement, drawing on the relational framework to demonstrate how entanglement manifests as a single grammatical structure rather than a causal connection between independent substances. Using QuTiP simulations, we visualized maximally entangled Bell states, reduced density matrices on Bloch spheres, Wigner functions of cat states, Fock distributions, and projective measurement statistics. Nested observer scenarios (Wigner’s friend) were modeled to contrast definite first-person reports with unitary third-person descriptions. Linguistic analysis drew on Saussurean semiotics and contemporary philosophy of physics to interpret visual results. Findings: Reduced density matrices of entangled subsystems are maximally mixed, showing no local definite properties, visualized as vanishing Bloch vectors. Wigner functions and Fock distributions exhibit non-classical interference, while joint measurements reveal perfect correlations as syntactic unfolding rather than causal influence. Wigner’s friend simulations confirm the Friend always experiences definite outcomes, whereas Wigner’s unitary view sustains superposed predication, exposing irreconcilable descriptive frames. Quantum phenomena resist classical subject-predicate grammar; entanglement and superposition embody relational, non-substantial structures whose correlations reflect pre-existing grammatical interdependence within the quantum langue, not mysterious action-at-a-distance. Recommendation: Future interpretations should prioritize relational ontologies that dispense with substantialist premises and develop formal languages capable of expressing quantum interdependence without smuggling classical predication. Empirical tests of relational predictions and interdisciplinary work bridging quantum foundations and semiotics are strongly encouraged.